The influence of political factors on commercial banks in Central European countries - Jackowicz, Krzysztof; Kowalewski, Oskar; Kozłowski, Łukasz (Journal of Financial Stability, 2013)
This study examines the impact of political factors on the behaviour and performance of commercial banks in 11 Central European countries from 1995 to 2008. Using a unique dataset of commercial banks and political factors, we find that state-owned banks report significantly smaller net interest income ratios during the years of parliamentary elections. The proxy cumulative amount of net interest income lost by state-owned banks during the election years equals, on average, 0.38% of each country's GDP. The decrease in the profitability of state-owned banks is caused primarily by the lower interest rates charged on loans. In contrast, we document that the lending growth of state-owned banks is not affected by the political cycle. Hence, to a certain extent, this study supports the view that state-owned banks constitute a tool that serves political goals in Central European countries.